Відділ білкової інженерії (Біополімери і клітина, 2004)
Відділ
створено
для
розвитку
нових
напрямків
молекулярної
біології,
таких
як
білкова
інженерія
і структурна
біоінформатика.
Основні
фундаментальні
дослідження
відділу
сконцентровано
на
вивченні
молекулярних
механізмів
дії
аміноацил-
тРНК
синтетаз
(APC)
вищих
еукаріотів
та
ролі
функціональної
динаміки
в
процесах
білково-нуклеїнового
впізнавання
Використовуються
методи
білкової
інженерії,
спрямовані
на
конструювання
нових
білків
із
зміненими
та
унікальними
властивостями.
Дизайн
білків
проводиться
для
вивчення
структурно-функціональної
ролі
окремих
амінокислотних
залишків,
мотивів
та
білкових
доменів.